Checks and Balances in Autoimmune Vasculitis - Hid Cadena, Rebeca; Abdulahad, Wayel H.; Hospers, G. A. P.; Wind, T. T.; Boots, Annemieke M. H.; Heeringa, Peter; Brouwer, Elisabeth (Frontiers in Immunology, 2018)
Age-associated changes in the immune system including alterations in surface protein expression, are thought to contribute to an increased susceptibility for autoimmune diseases. The balance between the expression of co-inhibitory and co-stimulatory surface protein molecules, also known as immune checkpoint molecules, is crucial in fine-tuning the immune response and preventing autoimmunity. The activation of specific inhibitory signaling pathways allows cancer cells to evade recognition and destruction by the host immune system. The use of immune checkpoint inhibitors (ICIs) to treat cancer has proven to be effective producing durable anti-tumor responses in multiple cancer types. However, one of the disadvantages derived from the use of these agents is the appearance of inflammatory manifestations termed immune-related adverse events (irAEs). These irAEs are often relatively mild, but more severe irAEs have been reported as well including several forms of vasculitis. In this article, we argue that age-related changes in expression and function of immune checkpoint molecules lead to an unstable immune system, which is prone to tolerance failure and autoimmune vasculitis development. The topic is introduced by a case report from our hospital describing a melanoma patient treated with ICIs and who subsequently developed biopsy-proven Giant Cell Arteritis. Following this case report, we present an in-depth review on the role of immune checkpoint pathways in the development and progression of autoimmune vasculitis and its relation with an ageing immune system.